Novel Star‐Shaped Benzotriindole‐Based Nonfullerene Donor Materials: Toward the Development of Promising Photovoltaic Compounds for High‐Performance Organic Solar Cells. Issue 3 (6th January 2022) - Rafiq, Arooza; Hussain, Riaz; Khan, Muhammad Usman; Mehboob, Muhammad Yasir; Khalid, Muhammad; Shehnaz,; Alam, Mohammed Mujahid; Imran, Muhammad; Ayub, Khurshid
Abstract : The development of novel photovoltaic materials for solar cell applications is a fascinating area of current research. Star‐shaped materials with promising photovoltaic features have attracted scientists for boosting the progress of organic solar cells (OSCs). Herein, seven novel star‐shaped molecules (DA1‐DA7) are developed quantum chemically from the experimentally synthesized BTI(2 T‐DCV‐Hex)3 molecule. The open‐circuit voltage ( V oc ), transition density matrix heat maps, density of state (DOS), overlap DOS, frontier molecular orbital, UV−visible, binding energy ( E b ), hole ( λ h ) and electron ( λ e ) reorganizational energy, and highest occupied molecular orbital (HOMO)donor −lowest unoccupied molecular orbital (LUMO)PC61BM charge transfer analysis are performed to explore the optoelectronic properties. Newly developed molecules exhibit promising optoelectronic features with reduced energy gap (2.43−1.97 eV), transition energy (1.89−1.45 eV), λ e (0.00149328−0.00101405 E h ), λ h (0.0066471−0.0028843 E h ), broadened λ max (655−856 nm), and high V oc (2.07−1.65 V), as compared with reference BTI(2 T‐DCV‐Hex)3 values 2.82 eV, 2.28 eV, 0.00176501 E h, 0.0060877 E h, and 544 nm, 1.65 V, respectively. The developed molecules have proficient hole and electron transfer mobilities and can serve as best candidates when blended with PC61 BM film. These eye‐catching results recommend the novel star‐shaped compounds for future development of high‐performance OSCs. Abstract : Seven novel star‐shaped molecules are quantum chemically developed from the experimentally synthesized BTI(2 T‐DCV‐Hex)3 molecule. The designed molecules have proficient optoelectronic features, excellent hole and electron transfer mobilities, and can serve as best candidates for solar cell applications when blended with a PC61 BM film.